PENGARUH MANAJEMEN BIAYA INTERNAL, INTEGRASI SISTEM INFORMASI EKSTERNAL DAN INTERNAL, SERTA KAPASITAS DAYA SERAP TERHADAP MANAJEMEN BIAYA ANTAR- ORGANISASI DALAM RANTAI PASOKAN (Studi Empiris pada Perusahaan Manufaktur di Provinsi Banten) - Gugun Gunawan Gugun Gunawan (LPPM STIA Banten, 2021)
Interorganizational cost management is a strategic cost management approach for managing costs that span organizational boundaries in a supply chain. Drawing on a resource-based view of the firm, we develop a model to predict the interrelated resources that enable firms to manage inter-organizational costs. We test this model using a survey of managerial accountants whose organizations are part of the supply chain. Using structural equation modeling, we conclude that internal e-integration resources, external e-integration, internal cost management, and absorption capacities play significant direct and indirect roles in the development of inter-organizational cost management (IOCM) resources. We find that these resources are interrelated and together are useful in enabling companies to benefit from managing costs across organizations. We find in particular the importance of relational resources related to absorptive capacity in IOCM resource development. Our research contributes to theory and practice by explaining how certain resources can be combined to enable companies to better manage costs between organizations. Data were analyzed using SEM with the help of SmartPLS version 3.0 software. This study uses the Field Research and Library Research methods, for data collection and data collection the researcher uses a purposive technique with standard classification criteria that have been determined to obtain accurate primary data based on the research theme taken. .